Design of class-E power amplifier for capacitive power transfer system. (October 2018) - Sun, Yanzhou; Yu, Jianghua; Liu, Xiaoqian
Abstract: High frequency power source is an indispensable part of capacitive power transfer system, and its performance plays an essential role in the overall system. Considering that class-E power amplifier is a prominent switched-mode power amplifier, and its power conversion efficiency can reach nearly 100%, theoretically. In this work, according to the requirements of capacitive power transfer system for power, the high efficiency class-E power amplifier as the AC source of the system has been designed. Firstly, the partial component parameters of class-E power amplifier can be calculated by circuit theory. Secondly, simulation circuits of the class-E power amplifier are designed by ADS software. Finally, an experimental prototype with the designed parameters is built up to verify the theory and simulation results. The experimental results show that the improved class-E power amplifier can reach work efficiency of 91% with 30 W output power, and capacitive power transfer system can achieve transfer efficiency of 76.2% with 25.15 W output power.